RETROPERITONEAL LAPAROSCOPIC DISMEMBERED PYELOPLASTY FOR URETEROPELVIC JUNCTION OBSTRUCTION (UPJO) - Daniswara, Nanda; Sibarani, Jupiter (Indonesian Urological Association, 2017)
Objective: To share our experience of retroperitoneal laparoscopic dismembered pyeloplasty as the treatment of Ureteropelvic Junction Obstruction (UPJO) in Department of Urology, Hasan Sadikin Hospital Bandung. Material & Methods: Boy 8 years old came for a chance to relieve mass at both flank region especially at left flank region. From the ultrasonography there were bilateral hydronephrosis. We decided to urethrocystoscopy, bilateral ureteral catether insertion, bilateral retrograd pyelography guided with c-arm and left retroperitoneal laparoscopic dismembered pyeloplasty. Results: Operative time was 240 minutes and blood loss was about 200cc. Double J Stent was used for ureteral stenting. Parenteral ketorolac was given as needed to control the pain. The Visual Analogue Scale (VAS) post operative day 1 until 4 were6, 4,, 2, 2 respectively. Urethral catheter was removed at post operative day 2 and drain was removed at post operative day 3. Operating wound was good. Patient was hospitalization until post operative day 4. Left nephrostomy was removed at postoperative day 7 after there was no leakage, confirmed with left antegrad pyelography. From post operative ultrasonography we found that hydronephrosis at left kidney became almost normal. Conclusion: In our opinion that the retroperitoneal laparoscopic dismembered pyeloplasty is an alternative treatment for UPJO. This procedure depends on experience and pristine surgical tehnique from the surgeon